Man, Science and Philosophy - Salgado Defranc, Eddy José (2011)
The analysis of the social history of science forces us to ask ourselves: why did science and philosophy appear in Greece, before in any other culture? What conditions led to its emergence and under what conditions? This article tries to analyze the events that occurred at the beginning of the first millennium to then review the main thinkers and philosophers, in order to establish a before and after of philosophy and, through their gaze, try to understand its origin and relevance. in history and in our current world.